Penerapan Metode Diskusi Berbantuan Lembar Kerja Siswa (LKS) untuk Meningkatkan Hasil Belajar Pendidikan Agama Hindu dan Budi Pekerti pada Siswa Kelas XI - Parthayasa, I Wayan Pica (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2022)
This study aims to determine the increase in learning outcomes of Hindu religious education and manners in class XI hotel accommodation students in the even semester of the 2021/2022 academic year through the application of the Student Worksheet Assisted Discussion method (LKS) at SMK Negeri 4 Mataram, Mataram City. This type of research is classroom action research which consists of two cycles. Each cycle consists of four stages, namely: 1) planning stage; 2) implementation stage; 3) the observation/evaluation stage; and 4) reflection stage. The subjects of this study were students of SMK Negeri 4 Mataram in class XI hospitality accommodation in the even semester of the 2021/2022 academic year as many as 23 people. Data on student learning outcomes were collected using the test method, and analyzed using descriptive statistics. Based on the results of data analysis and discussion of research results, that the learning outcomes of Hindu religious education and character in class XI hotel accommodation students in the even semester of the 2021/2022 academic year have increased through the application of the Student Worksheet Assisted Discussion method (LKS) at SMK Negeri 4 Mataram, with the average student learning outcomes in the first cycle of 76.79% increased by 4.28% to 81.07% in the second cycle. So, it can be concluded that the application of the discussion method assisted by Student Worksheets (LKS) can improve learning outcomes of Hindu religious education and manners in class XI students of hospitality accommodation in the even semester of the 2021/2022 academic year at SMK Negeri 4 Mataram.